Agronomical indicators for determination of potato (Solanum tuberosum L.) tolerance to drought - Alfredo Morales Rodríguez; Alfredo Morales Tejón; Dania Rodríguez del Sol (Agrisost, 2016)
Lately, water shortage has caused 50% losses in potato yields in several Central American countries. Knowledge and use of more tolerant potato varieties are a critical element to increase production and yields under stressing conditions. The experiments were developed at the Center for Tropical Crops Research (INIVIT), between December 2014, and March 2015. Ten plots were planted, including different varieties. Half of them (5) were not irrigated for 20 days, starting on the 50th day after plantation (drought stress period). Irrigation was resumed on the 70th day. The Stress Susceptibility Index (SSI), Stress Tolerance Index (STI), Tolerance Index (TOL), Mean Productivity (MP), and Yield Stability Index (YSI). The Atlas and Maranca varieties had the lowest values for SSI (0.67 and 0.61, respectively), and the highest values for STI (0.79 and 0.81, respectively). The highest MP (19.92 t/ha) was achieved by Atlas. The highest YSI values were observed in Maranca and Atlas (81.07 and 79.29, respectively).